2012
DOI: 10.1002/andp.201100274
|View full text |Cite
|
Sign up to set email alerts
|

The inhomogeneous extended Bose‐Hubbard model: A mean‐field theory

Abstract: Dedicated to Ulrich Eckern on the occasion of his 60th birthday.We develop an inhomogeneous mean-field theory for the extended Bose-Hubbard model with a quadratic, confining potential. In the absence of this potential, our mean-field theory yields the phase diagram of the homogeneous extended Bose-Hubbard model. This phase diagram shows a superfluid (SF) phase and lobes of Mott-insulator (MI), density-wave (DW), and supersolid (SS) phases in the plane of the chemical potential μ and on-site repulsion U ; we pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 32 publications
(56 reference statements)
3
42
0
2
Order By: Relevance
“…[61,65]. We have also checked the spin eigenvalues and the order parameter profiles in presence of one dimensional trapping potential without zV/U 0 in both the AF and ferromagnetic cases are in agreement with the results obtained in ref.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…[61,65]. We have also checked the spin eigenvalues and the order parameter profiles in presence of one dimensional trapping potential without zV/U 0 in both the AF and ferromagnetic cases are in agreement with the results obtained in ref.…”
Section: Resultssupporting
confidence: 89%
“…To decouple both the hopping and the density-density interaction terms, we use the mean field approximation as given by, [20,61] …”
Section: Modelmentioning
confidence: 99%
“…6 exhibit a small region where both phases spatially overlap. Other studies [39,40] with different systems in the presence of a harmonic trap have shown coexistence of phases without spatial overlapping, for instance, in the extended Bose-Hubbard model the Mott insulator and superfluid phases tend to form rings and disks. In 2D those studies agree quantitatively with Quantum Monte Carlo calculations and more Finally, when the interlayer spacing is large enough, the intralayer repulsive interaction dominates over the interlayer attraction and the superfluid order parameter almost vanishes.…”
Section: Supersolid: Coexistence Of Superfluid and Density Ordermentioning
confidence: 99%
“…(iv) i and j both even : no neighbours To find the ground state properties of the system, first we have computed the matrix elements of the Hamiltonian in Eq. (3) in the occupation number basis |n truncated at some number n max (n max = 8 used here) [9,10] and diagonalize it to obtain the self consistent values of ψ i and ρ i . It is equivalent to the minimization of free energy of the system.…”
Section: Model and Formalismmentioning
confidence: 99%
“…[9]. In presence of trapping potential, it was extended for the inhomogeneous case for a bipartite lattice [10]. In a previous work, we have considered a tripartite lattice and solved extended Bose Hubbard model (EBHM) via mean field theory in the homogeneous case and obtained a rich phase diagram, in which the ground state of the model exhibits SF, different density ordered (DW), supersolid (SS) and MI phases as function of the chemical potential [11].…”
Section: Introductionmentioning
confidence: 99%